FORMULASI KAPSUL DAUN DAN BIJI JAMBLANG (Syzigium cumini L.) SEBAGAI ANTIOKSIDAN ALAMI DARI DESA PALLANTIKANG KABUPATEN MAROS - Siti Nurhalisa (Jurnal Medika Hutama, 2021)
This research was conducted to test the antioxidant activity of leaf and seed capsules jamblang (Syzigium cumini L.). The research was carried out in stages including sampling, sample preparation, capsule making, organoleptic testing (aroma, color and taste), observation of water content, and testing antioxidant activity using the free radical scavenging method DPPH (2,2-diphenyl-1-picrylhydrazil) and UV-Vis spectrophotometry. Antioxidant activity was tested using the DPPH method (2,2-diphenyl-1-picrylhydrazyl) method. Antioxidant activity test results showed that IC50 (Inhibitory Concentration) jamblang leaf (Syzigium cumini L.) capsules was 14,68 (very active) and jamblang seeds (Syzigium cumini L.) capsules was 19,68 (very active). AAI values (Antioxidant Activity Index) jamblang leaf (Syzigium cumini L.) capsules 6,8 (very strong) and jamblang seed (Syzigium cumini L.) capsules was 5,1 (very strong). Based on this study, jamblang leaf (Syzigium cumini L.) capsules have higher antioxidant activity than jamblang seeds (Syzigium cumini L.) capsules.